Murder in Gotham - Haiblum, Isidore (New York : Berkley Prime Crime, 2008)
Instead of the police, the wife of a missing man asks detective Morris Weiss for help. He knows more than the cops about the gangland workings of the Lower East Side -- and he's about to learn even more.
Keywords: Missing persons -- Fiction; Private investigators -- Fiction; Lower East Side (New York, N.Y.) -- Fiction; Mystery fiction